2020
DOI: 10.1111/jdv.16203
|View full text |Cite
|
Sign up to set email alerts
|

Circulating microRNAs in extracellular vesicles as potential biomarkers for psoriatic arthritis in patients with psoriasis

Abstract: Background Psoriatic arthritis (PsA) develops in~30% of patients with psoriasis. The diagnosis of PsA is challenging, and there are no reliable molecular markers in clinical use. MicroRNAs are short non-coding regulatory RNAs, which can be actively packaged into extracellular vesicles (EVs) and secreted to the circulation. Objectives To explore whether plasma-derived EV microRNAs may serve as biomarkers for PsA in patients with psoriasis. Methods Plasma samples were obtained from patients with cutaneous-only p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
28
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 52 publications
(28 citation statements)
references
References 54 publications
0
28
0
Order By: Relevance
“…Of those 14 markers, six showed a positive association with the presence of PsA in Pso: the presence of anti-citrullinated protein antibodies (ACPA) [ 37 40 ], a higher level of IL-34 [ 56 , 66 ], a higher level of tumor necrosis factor alpha (TNFα) [ 56 , 64 ], a higher mean platelet volume (MPV) [ 68 , 69 ], a higher LDL:HDL ratio [ 62 , 64 , 71 , 76 ], and the presence of microRNA miR-146a-50 [ 78 , 79 ].…”
Section: Resultsmentioning
confidence: 99%
“…Of those 14 markers, six showed a positive association with the presence of PsA in Pso: the presence of anti-citrullinated protein antibodies (ACPA) [ 37 40 ], a higher level of IL-34 [ 56 , 66 ], a higher level of tumor necrosis factor alpha (TNFα) [ 56 , 64 ], a higher mean platelet volume (MPV) [ 68 , 69 ], a higher LDL:HDL ratio [ 62 , 64 , 71 , 76 ], and the presence of microRNA miR-146a-50 [ 78 , 79 ].…”
Section: Resultsmentioning
confidence: 99%
“…Here, we present a workflow for nCounter-based analysis of plasma-derived EVs and we demonstrate that it can be used to efficiently detect transcripts in EV-enriched preparations from cancer patients and control samples. The first step of the workflow is plasma processing using the precipitation-based miRCURY kit which, as previously described 29,30 , yielded pellets enriched in EVs. Clinical laboratories do not usually have access to ultracentrifugation and precipitation kits offer several advantages, such as short turn-around time and limited technical requirements.…”
Section: Discussionmentioning
confidence: 99%
“…Many studies have shown that endothelial and platelet-derived EVs are elevated in patients with psoriasis [ 50 , 51 , 52 ]. Recently, potential biomarkers of psoriasis are being discovered through miRNA profiling analysis of plasma-derived EVs [ 53 , 54 ]. AD, one of the eczemas, is another common chronic inflammatory skin disease.…”
Section: The Role and Therapeutics Potential Of Extracellular Vesicles In Inflammatory Diseasesmentioning
confidence: 99%